2021
DOI: 10.1016/j.ajpath.2021.05.004
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning-Based Approach for Glomeruli Instance Segmentation from Multistained Renal Biopsy Pathologic Images

Abstract: Glomeruli instance segmentation from pathologic images is a fundamental step in the automatic analysis of renal biopsies. Glomerular histologic manifestations vary widely among diseases and cases, and several special staining methods are necessary for pathologic diagnosis. A robust model is needed to segment and classify glomeruli with different staining methods and apply in cases with various glomerular pathologic changes. Herein, pathologic images from renal biopsy slides stained with three basic special sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 25 publications
(19 reference statements)
0
21
0
Order By: Relevance
“…Currently, DL has enabled rapid advances in computational pathology ( 11 , 12 ). For example, DL methods have been applied to segment and classify glomeruli with different staining and various pathologic changes, thus achieving the automatic analysis of renal biopsies ( 13 , 14 ); meanwhile, DL-based automatic colonoscopy tissue segmentation and classification have shown promise for colorectal cancer detection ( 15 , 16 ); besides, the analysis of gastric carcinoma and precancerous status can also benefit from DL schemes ( 17 , 18 ). More recently, for the ALN metastasis detection, it is reported that DL algorithms on digital lymph node pathology images achieved better diagnostic efficiency of ALN metastasis than pathologists ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, DL has enabled rapid advances in computational pathology ( 11 , 12 ). For example, DL methods have been applied to segment and classify glomeruli with different staining and various pathologic changes, thus achieving the automatic analysis of renal biopsies ( 13 , 14 ); meanwhile, DL-based automatic colonoscopy tissue segmentation and classification have shown promise for colorectal cancer detection ( 15 , 16 ); besides, the analysis of gastric carcinoma and precancerous status can also benefit from DL schemes ( 17 , 18 ). More recently, for the ALN metastasis detection, it is reported that DL algorithms on digital lymph node pathology images achieved better diagnostic efficiency of ALN metastasis than pathologists ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…This network was trained to classify glomeruli into three categories, including normal glomeruli, sclerotic glomeruli, and glomeruli with other lesions. Using this network, the F1-score of the subgroups achieved 0.68–0.90 in the snapshot group, and the score reached a comparable level (0.75–0.83) in the WSI group [ 43 ]. In addition, new AI-assisted technique applications have been reported in recent studies, such as non-label classification and fine-grained characterization of glomerulosclerosis in renal biopsy pathological images [ 44 , 45 ].…”
Section: Application Of Ai In Nephropathologymentioning
confidence: 99%
“…One of the most frequent use of cases of machine learning for histopathologic analysis is to extract the glomeruli and ascertain key histologic findings [33,34]. Manual assessment of glomerular sclerosis, a primary manifestation in a spectrum of kidney diseases and an important component of disease staging, requires expertise that may be lacking in resource-limited settings and introduces intrareader and inter-reader variability in interpretations.…”
Section: Histopathologymentioning
confidence: 99%